2017
DOI: 10.1007/s00592-017-1001-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of proliferative markers in pancreatic β-cells of patients with severe hypoglycemia following Roux-en-Y gastric bypass

Abstract: Aims Severe postprandial hypoglycemia with neuroglycopenia is an increasingly recognized, debilitating complication of Roux-en-Y gastric bypass (RYGB) surgery. Increased secretion of insulin and incretin hormones are implicated in its pathogenesis. Histopathologic examination of pancreas has demonstrated increased islet size and/or nuclear diameter in post-RYGB patients who underwent pancreatectomy for severe refractory hypoglycemia with neuroglycopenia (RYGB+NG). We aimed to determine whether β-cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
9
1
4
Order By: Relevance
“…This may explain, in part, the absence of nuclear MAFA expression in pancreas sections from T2D patients while expression remained in human ducts that were obtained from controls without diabetes and transplanted into mice. Alternatively, this may be an example of heterogeneity that is observed in pathological conditions affecting the pancreas (53).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain, in part, the absence of nuclear MAFA expression in pancreas sections from T2D patients while expression remained in human ducts that were obtained from controls without diabetes and transplanted into mice. Alternatively, this may be an example of heterogeneity that is observed in pathological conditions affecting the pancreas (53).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analyses revealed no differences in overall b-cell mass when the same samples were compared with autopsy specimens (36). Other studies revealed substantial variability in both b-cell area and markers of proliferation (37). Whether these differences reflect heterogeneity in the population under study or are unrelated to functional differences in mealstimulated insulin responses remains uncertain.…”
Section: Pathophysiology Of Pbhmentioning
confidence: 95%
“…However, a small study involving Goto-Kakizaki rats showed no increase in β -cell mass after sleeve gastrectomy and duodenal-jejunal bypass [33]. In a human study, pancreatic tissue obtained from patients with symptomatic postprandial hypoglycemia after RYGB did not show increased β -cell mass [34], although others have reported opposite results [3, 4, 35]. Given these discrepant results, the important question of whether RYGB causes changes in β -cell mass is still open.…”
Section: Discussionmentioning
confidence: 99%